Controllable Formation of Si Nanostructures Based on Quasi-Plasmonic Planar Nanostructures Formed by Annular-Shaped Femtosecond Laser Pulse - Weina Han; Dongfang Li; Furong Liu; Yanping Yuan; Xiaowei Li (IEEE Photonics Journal)
We demonstrate the feasibility to control the confined electromagnetic field by surface plasmon poloritons (SPPs) excitation and scattering modulation based on the pre-processed Au nanostructures under the irradiation of single-shot femtosecond (fs) laser pulse, and then to control the surface tension-induced molten Si transport due to the directed lateral temperature profile, thus resulting in the formation of Si nanostructures. Annular-shaped fs laser pulse is employed based on nonlinear optical effect of frequency-doubling process to imprint Au planar nanostructures with various morphologies. Because surface plasmon polaritons can be easily excited and controlled on planar nanostructures of noble metals, the localized electromagnetic field can be effectively modulated by controlling the metallic nanostructures. Thus, the quasi-plasmonic Au nanostructures act as precursors for controlling the subsequent electromagnetic field by fs laser irradiation. Upon irradiation of pre-processed Au nanostructures, confined electromagnetic field induces a specific surface tension profile, causing directional transport of molten Si. After solidification, Si nanostructures of controllable morphologies can be fabricated. Simulation results are in agreement with the theoretical mechanism. Moreover, further optimized modulation of nanodome can be achieved by controlling the focus spot control combined with the polarization state control. This paper provides an effective method for enabling a scalable formation of Si nanostructures.